2009
DOI: 10.1002/mop.24823
|View full text |Cite
|
Sign up to set email alerts
|

Compact rat‐race ring coupler with capacitor loading

Abstract: A simple compact microstrip rat-race ring coupler with capacitor loading is presented in this letter. The new coupler not only effectively reduces the occupied area to 15% of the conventional one at 1.0 GHz, but also has high harmonic suppression performance over a wide band. Furthermore, the new structure has only two variable parameters and can be easily designed. The design is validated both by simulation and measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…The rat-race coupler topology proposed by Wei Shao et al [14] was similar to one reported by Jen-Tsai Kuo et al [15] in great part. As Figure 10(b) illustrates, there is no obvious slot and thin stub in the ring resonator.…”
Section: Harmonic Suppressionmentioning
confidence: 81%
See 1 more Smart Citation
“…The rat-race coupler topology proposed by Wei Shao et al [14] was similar to one reported by Jen-Tsai Kuo et al [15] in great part. As Figure 10(b) illustrates, there is no obvious slot and thin stub in the ring resonator.…”
Section: Harmonic Suppressionmentioning
confidence: 81%
“…Completely different from the principles of [12] and [13], capacitive loading [14] was proposed instead of a periodic stepped-impedance ring resonator [15] to synthesize a compact rat-race coupler with harmonic suppression. As Figure 10(a) illustrates, six flabelliform patches are located inside the open area of the ratrace coupler and are connected to a high-impedance TL through a short, thin stub.…”
Section: Harmonic Suppressionmentioning
confidence: 99%
“…Up to date, numerous approaches have been developed for compact RRCs, e.g., using capacitor [13] and periodic slow-wave loading [14], using periodic stepped-impedance ring resonators [15], T-shaped photonic bandgap (PBG) structures [16] and fractal strategy [17][18][19]. Although above RRCs feature compact, the lack of dual band (DB) performances deserves further improvements.…”
Section: Dual Band Rat-race Couplermentioning
confidence: 99%
“…In [3], though great size reduction was achieved and the band-rejection response was wide, the lower harmonic suppression should be further improved and the depth of harmonic suppression was merely below −15 dB in the stopband. In [4], the harmonic suppressed was very limited, just the second and third. In order to achieve great size reduction and harmonic suppression, simultaneously, a new low-pass filter (LPF) unit cell (LUC) is integrated into rat-race coupler design.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [1,2] dedicated themselves into the size reduction research, but the importance of the harmonic suppression was ignored. To realize both harmonic suppression and size reduction, some attempts [3,4] were made. In [3], though great size reduction was achieved and the band-rejection response was wide, the lower harmonic suppression should be further improved and the depth of harmonic suppression was merely below −15 dB in the stopband.…”
Section: Introductionmentioning
confidence: 99%